Analisis Ekonomi Islam dalam Perspektif Fiqh Melalui Kajian Qawaidul Fiqhiyyah - Mustofa Mustofa, Mustofa; Fuji Hakiki, Muhamad; Suganda, Ahmad; Rahman, Encep Taufik (EKALAYA : Jurnal Ekonomi Akuntansi, 2024)
Islamic economics, as a component of Islamic knowledge, has emerged as a new discipline in the social sciences, gaining recognition in various higher education institutions in the contemporary Muslim world. Various sources of Islamic knowledge have played an important role in shaping its growth and progress. However, the principles of Islamic law, especially qawa'id al-fiqhiyyah, have not been widely explored regarding their application in the current fiqh paradigm. Through a content analysis approach, this paper examines the relevance of qawā'id al-fiqhiyyah, specifically focusing on the five normative principles and their variations, in understanding Islamic economics from a fiqh perspective. The aim is to evaluate its significance in Islamic economic activities and its adaptability in different temporal and spatial contexts. This research reveals that qawa'id al-fiqhiyyah significantly enriches the understanding of Islamic economics in the realm of higher education. These principles help in interpreting economic theories through the lens of Islamic ethics. Therefore, it can be concluded that the concerted efforts of Muslim social scientists, especially economists, to study this branch of fiqh diligently and with dedication will facilitate a deeper understanding of economic theories from the perspective of fiqh.